On Flow Characteristics and Interpretative Methods of Oil-Water Two-Phase Flow in Slightly Negative Angle Deviated Pipes - QIN Hao; ZHANG Haining; DUAN Chaowei; LIU Chunlei; TANG Jin; LI Fan; WANG Hang (Cejing jishu)
The difference of flow characteristics makes the conventional production logging interpretation model unable to accurately predict the true flowrate of each phase in horizontal wells. Combined with the computational fluid dynamics simulation technology, the effects of input parameters on the flow characteristics of phase distribution and velocity distribution of oil-water two-phase flow in large diameter deviated pipes are studied. Furthermore, the relationship of characteristic flow parameters is analyzed. As well as, the interpretative model for production logging data of oil-water two-phase flow in slight deviated pipe is established, and the model is verified with the logging data of a horizontal wells. The results shown that:①The flow pattern of oil-water two-phase in a slightly downward pipe is mainly stratified flow, and with the increasing of inclination angle and inlet water content, the flow pattern gradually transitions to mixed interface flow and oil in water oil flow;②The retention characteristics of oil phase increase with the increase of inlet water content and downward inclination angle of flow pipe; and the oil phase will be backflow when the downward inclination is greater than 10 ° and the input water is larger than 0.8;③The coefficient of phase distribution and drift velocity are affected by the inclination angle of the flow pipe. A predictive model for fluid velocity of each phase with the correction of the inclination angle is established. And the verification results of the well data show that the new model has a high prediction accuracy. The research enriches the theory of multiphase flow and has certain reference significance for the research of production performance monitoring technology and logging data interpretation method of horizontal wells.